Penerapan Metode Pembelajaran Think Pair Share dalam Pendidikan Agama Katolik - Sergius Lay (Jurnal Magistra, 2025)
Catholic Religious Education (CRE) plays a vital role in shaping students’ character, morality, and spirituality. However, traditional and monotonous teaching approaches often lead to passive student engagement and low motivation. This article explores the implementation of the Think Pair Share (TPS) method in CRE as an innovative, cooperative, and student-centered learning strategy. Utilizing a literature review method, this study analyzes various scholarly sources related to TPS and Catholic religious education. The findings indicate that the TPS method encourages students to think critically, engage in peer discussions, and confidently share ideas in class, thereby creating an active and inclusive learning environment. Nevertheless, the effectiveness of this method depends greatly on the teacher’s readiness in lesson planning, fostering a supportive classroom atmosphere, and providing constructive feedback. Adaptive and creative teaching strategies are essential to ensure that TPS is effectively and meaningfully applied within the context of CRE in the era of independent learning.